Increased TNF-α Initiates Cytoplasmic Vacuolization in Whole Blood Coculture with Dengue Virus. (7th May 2021) - Satria, Rahmat Dani; Huang, Tzu-Wen; Jhan, Ming-Kai; Shen, Ting-Jing; Tseng, Po-Chun; Wang, Yun-Ting; Yang, Zhen-Yu; Hsing, Chung-Hsi; Lin, Chiou-Feng
Abstract : During the acute febrile phase of dengue virus (DENV) infection, viremia can cause severe systemic immune responses accompanied by hematologic disorders. This study investigated the potential induction and mechanism of the cytopathic effects of DENV on peripheral blood cells ex vivo . At one day postinfection, there was viral nonstructural protein NS1 but no further virus replication measured in the whole blood culture. Notably, DENV exposure caused significant vacuolization in monocytic phagocytes. With a minor change in the complete blood cell count, except for a minor increase in neutrophils and a significant decrease in monocytes, the immune profiling assay identified several changes, particularly a significant reduction in CD14-positive monocytes as well as CD11c-positive dendritic cells. Abnormal production of TNF- α was highly associated with the induction of vacuolization. Manipulating TNF- α expression resulted in cytopathogenic effects. These results demonstrate the potential hematological damage caused by ex vivo DENV-induced TNF- α .